Optimizing Financial Management: A Priority in Improving Efficiency and Transparency in High School - Laksono, Arief; Ayu, Sovia Mas; Sari, Putri Permata; Asy'arie, Bima Fandi; Achmadin, Balya Ziaulhaq (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
The purpose of this study is to determine and analyze the management of educational finance as a fulfillment of facilities and infrastructure in order to increase efficiency and transparency at SMA Negeri 1 Katibung, South Lampung Regency. This study uses a qualitative approach with a case study method. Based on findings in the field, SMAN 1 Katibung has implemented a fairly good financial management system. The discussion in this study highlights the importance of school financial management which includes (1) budget planning, (2) fund allocation, (3) funding sources, (4) supervision and transparency, (5) maintenance and development, (6) evaluation and reporting. However, one of the main obstacles that often arises in school financial management is related to fund allocation. This is due to the large number of maintenance needs for facilities and infrastructure and efforts to develop facilities that must be maintained and cared for optimally so that they continue to function properly. Thus, a sense of responsibility and ownership of facilities and infrastructure is needed as an effort to maintain, supervise and assist so that the use of facilities and infrastructure can be in accordance with the expected goals.